The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/slct.202104183
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Reactive Dyes Using Flyash Supported Ag‐TiO2 Photocatalysts

Abstract: In the present study, photocatalytic degradation of five different reactive dyes has been carried out using Ag doped TiO 2 supported on coal fly ash (CFA) as a photo catalyst system (Ag-TiO 2 /CFA). The photocatalysts were synthesized with varying the percentage of Ag and characterized by XRD, SEM and UVvisible spectrophotometry. The photocatalytic activity of Ag-TiO 2 /CFA photocatalysts was studied for the degradation of reactive dyes in presence of both UV and visible light sources. The degradation was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…The peaks of the anatase TiO 2 of catalytic materials appear at 2θ values of 25.3° (101), 37.8° (004), 48.1° (200), 53.8° (105), 55.2° (211) and 63.0° (204). TiO 2 supported on cellulose metallized showed anatase form indicating it has not changed its crystal structure [38,39] . The XRD pattern of the total composite showed the same diffraction peaks of both Ni and anatase TiO 2 , which indicated that the composite was successfully formed.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The peaks of the anatase TiO 2 of catalytic materials appear at 2θ values of 25.3° (101), 37.8° (004), 48.1° (200), 53.8° (105), 55.2° (211) and 63.0° (204). TiO 2 supported on cellulose metallized showed anatase form indicating it has not changed its crystal structure [38,39] . The XRD pattern of the total composite showed the same diffraction peaks of both Ni and anatase TiO 2 , which indicated that the composite was successfully formed.…”
Section: Resultsmentioning
confidence: 87%
“…TiO 2 supported on cellulose metallized showed anatase form indicating it has not changed its crystal structure. [38,39] The XRD pattern of the total composite showed the same diffraction peaks of both Ni and anatase TiO 2 , which indicated that the composite was successfully formed.…”
Section: Chemistryselectmentioning
confidence: 83%
“…Titanium dioxide (TiO 2 ) is a semiconductor substance that is frequently used in photocatalytic applications. [200][201][202] As a result, it is the catalyst of choice for degrading dyes into mineralization compounds due to its widespread availability, chemical stability, good optical transparency, high refractive index, and ecologically acceptable nature. [203] Nanocatalysts, unlike catalysts, have a higher surface area, which allows for better surface-volume interaction and, as a result, better adsorption properties.…”
Section: Photocatalytic and Photo-electrocatalytic Processesmentioning
confidence: 99%
“…reported the photodegradation of malachite green with the help of fabricated lanthanum‐ferrite (LaFeO 3 ) perovskite oxide (PO) obtained from the Terminalia arjuna leaf. Titanium dioxide (TiO 2 ) is a semiconductor substance that is frequently used in photocatalytic applications [200–202] . As a result, it is the catalyst of choice for degrading dyes into mineralization compounds due to its widespread availability, chemical stability, good optical transparency, high refractive index, and ecologically acceptable nature [203] …”
Section: Treatment Of Textile Dyesmentioning
confidence: 99%
“…[9,10] Heterojunctions between metals and TiO 2 photocatalysts can enhance the interfacial charge-transfer performance and thereby its absorption edge can be extended to the visible light region. [11,12] Among metal ions, Co 2 + is one of the most efficient dopants due to its optically active nature; doping Co 2 + could improve the light response and help to boost the performance of TiO 2 . [13,14] Recently, studies on cobalt-doped TiO 2 photocatalysts have indicated significant performance in the degradation of a wide variety of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%